Illness Fatality in Welding Process (Case Report) - Arriz Akbar Sukadi; Nuri Purwito Adi (The Indonesian Journal of Community and Occupational Medicine, 2022)
Cardiac arrest is a condition where there is a sudden cessation of cardiac activity, causing a person to become unresponsive to calls/stimuli. If there is no immediate corrective action (Cardiopulmonary Resuscitation and/or defibrillation), this condition will be fatal and can progress to sudden death. A 32-year-old young man who had just worked welding pipes while working at PT.X experienced a cardiac arrest, where there was no breathing and no pulse. It is known that there are several exposures that can be found during the welding process, so it is necessary to carry out an investigation to assess the possible causes of the condition, whether it is due to occupational factors or pre-existing diseases in workers. This case study report focuses on exploring the possible causes of cardiac arrest in this young worker in accordance with his duties as a welder and recommendations for what needs to be done to prevent similar incidents from happening in the future. This case study will also help in creating awareness regarding the need for Daily Check Up monitoring in high-risk workers such as welders.